XIth International Congress on Thrombosis and Haemostasis 1987
DOI: 10.1055/s-0038-1643593
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Optimal Dosage of LMW Heparin in the Sc Treatment of Deep Venous Thrombosis

Abstract: LMW heparin (LMWH) is better suited for subcutaneous (sc) administration than is UF heparin due to higher bioavailability and slower elimination. Optimal dosage for sc treatment of DVT has not been defined. Our previous study suggested that LMWH should be given in doses according to bodyweight (bw), and that sc injection of 100 anti-Xa U/kg bw/12 hrs might result in therapeutic plasma levels (Holm et al. Haemostasis 16, supl 2,30-37, 1986). This dosage is now being evaluated in an open study including patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, with the twice daily regi men, the trough levels of the corresponding dalteparin dose (0.51, 0.34-0.82 IU/ml) did not reach the minimum desired anti-FXa lev el implying that a s.c. dalteparin dose of 100 IU/ml administered b.i.d. is not sufficient to cover 12 h as regards proposed therapeutic levels of anti-FXa activity [ 18,19] In all patient groups in our study we ob served a transient increase of the APTT value, peaking during the first 24 h. This observa tion is probably explained by streptokinaseinduced depletion of fibrinogen, coagulation factors V and VIII. Also, the appearance of anticoagulant fibrin(ogen) degradation prod ucts can affect the APTT value [21].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…However, with the twice daily regi men, the trough levels of the corresponding dalteparin dose (0.51, 0.34-0.82 IU/ml) did not reach the minimum desired anti-FXa lev el implying that a s.c. dalteparin dose of 100 IU/ml administered b.i.d. is not sufficient to cover 12 h as regards proposed therapeutic levels of anti-FXa activity [ 18,19] In all patient groups in our study we ob served a transient increase of the APTT value, peaking during the first 24 h. This observa tion is probably explained by streptokinaseinduced depletion of fibrinogen, coagulation factors V and VIII. Also, the appearance of anticoagulant fibrin(ogen) degradation prod ucts can affect the APTT value [21].…”
Section: Discussionmentioning
confidence: 70%
“…Plasma concentra tions ranging between 0.4 and 2.0 anti-FXa IU/ml have been obtained following subcuta neous dalteparin doses of 240-480 IU/kg b.w./24 h [ 17], Other studies have shown that mean plasma levels in the range of 0.6-1.0 anti-FXa IU/ml are comparable to high-dose unfractionated heparin regarding antithrom botic effect without causing bleeding compli cations in patients with deep-venous throm bosis [18,19]. Another dose-finding study evaluating different doses (240-360 IU/kg b.w./24 h) of dalteparin in AMI verified the range of 0.6-1.0 anti-FXa IU/ml to be effec tive also regarding prevention of left-ventricu lar thrombi [20].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In recent years, low-molecular-weight (LMW) derivatives of commercial heparin have been prepared that have a mean molecu lar weight of 4,000-5,000 daltons in contrast to unfractionated heparin, which has a mean molecular weight of 12.000-16,000 daltons [19,20], Pharmacokinetic studies [21][22][23][24][25][26], and recent small clinical trials in selected patients with venous thrombosis [27][28][29][30][31], in dicate that the bioavailability of these LMW heparin fractions following subcutaneous in jection is very' high. For example, Bratt et al [23] reported that the bioavailability of LMW heparin after a subcutaneous injection of 120 factor Xa units per kilogram to healthy volun teers was approximately 90% of an equivalent intravenous dose.…”
Section: Introductionmentioning
confidence: 99%